A new species of spiders of the genus Zelotes Gistel, 1848 (Aranei: Gnaphosidae) from the North-East Pre-Caspian region - A.V. Ponomarev (Кавказский энтомологический бюллетень, 2018)
A new spider species  Zelotes abdurakhmanovi sp.  n.  (Gnaphosidae) is described from the North-East Pre-Caspian region (Tyub Karagan Cape, Kulaly Island, Kazakhstan). This new species belongs to the puritanus species  group and close to Mediterranean Z. laetus (O. Pickard-Cambridge, 1872) by the structure of the epigyne and Z. gussakovskyi Charitonov, 1951, described from Tajikistan by the structure of male palp. A  new species characterized by the narrow, long, parallel-sided plate of the epigyne (not liguliform as in Z. laetus); the most part of embolus is located on the dorsal side of the tegulum; the loop of the embolus forms almost a semicircle, covering almost the entire width of the distal part of the tegulum (other species of this group have the loop much narrower and shifted to the edge of the tegulum)